1998
DOI: 10.1007/s004310050911
|View full text |Cite
|
Sign up to set email alerts
|

Risk and preventive factors for cot death in The Netherlands, a low-incidence country

Abstract: Placing an infant prone or on side on last occasion, secondary prone position (not placed prone but turned to prone), inexperienced prone sleeping and use of a duvet, leading to head and body being covered, were shown to be risk factors. Preventive factors were using a cotton sleeping-sack and a dummy. Even in a low incidence country, such as the Netherlands, there are indications that further prevention is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 21 publications
2
78
0
Order By: Relevance
“…45 Loose bedding, particularly when the infants' heads become covered, has been associated with SIDS, even in supine sleeping infants. 12,16,17,20 Infant sleep clothing may be an appropriate alternative to blankets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Loose bedding, particularly when the infants' heads become covered, has been associated with SIDS, even in supine sleeping infants. 12,16,17,20 Infant sleep clothing may be an appropriate alternative to blankets.…”
Section: Discussionmentioning
confidence: 99%
“…Soft bedding increases the potential of rebreathing, [1][2][3][4][5][6] a pathway through which SIDS may occur. 7 Pillows, quilts, comforters, and other soft objects are hazardous when placed under the infant [8][9][10][11][12][13][14][15] or loose in the infant's sleep area, 10,12,[15][16][17][18][19][20] increasing SIDS risk up to 5-fold, 13,15 and up to 21-fold when the infant is placed prone. 15 However, use of soft bedding and surfaces is common.…”
mentioning
confidence: 99%
“…E pidemiologic studies identifying risk factors and public health campaigns to reduce these risks have been followed by large reductions in the rates of sudden infant death syndrome (SIDS) in many countries. [1][2][3][4][5][6][7][8][9][10] In Reduce the Risk public health campaigns, priority has been given to risk factors that may be causally related to SIDS. 11,12 In addition, priority has been given to risk factors that are readily correctable and at the same time acceptable to care providers and parents.…”
mentioning
confidence: 99%
“…Rather, we describe the frequency with which well-established risk factors are evident from the death-scene investigation. 4,10,18,20,21 This study has focused on 4 sleep practices as risk factors: position when found, 22 presence of bedding or other materials covering the infant's face or head, 18,20 sharing a sleep surface with others, [23][24][25][26][27][28][29] and the use of sleep surfaces other than those recommended for infants. 14,15,17 In addition to the strong consensus regarding their effect on risk, we have focused on these 4 sleep practices because the death-scene data provided detailed information about them, and because these risk factors might be eliminated through information campaigns.…”
mentioning
confidence: 99%
“…We examined 17 observational studies (Table 1) and found that breastfeeding was reported to have provided a protective effect on SIDS in ten studies 6, 7, 8, 9, 10, 11, 12, 13, 14, 15. No protective effects were found in the other seven 4, 16, 17, 18, 19, 20, 21.…”
Section: Resultsmentioning
confidence: 99%